2004
DOI: 10.1057/palgrave.jgm.4940004
|View full text |Cite
|
Sign up to set email alerts
|

Promotion, Information and Advertising: Why Increasingly Blurred Boundaries do not Benefit the Public

Abstract: Jackie Glatteris a senior public affairs off|cer specialising in health issues at Consumers' Association. As Europe's largest independent consumer organisation, Consumers' Association produces an extensive range of publications ö including Drug and Therapeutics Bulletin, Treatment Notes and Which? magazine ö and campaigns to achieve improvements in goods and services.Abstract Recent legislative proposals from the European Commission to relax the prohibition on direct-to-consumer advertising (DTCA) of prescript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…DAA has been identified as a form of disease mongering or “widening the boundaries of treatable illness in order to expand markets for those who sell and deliver treatments” 4 . DAA is often directed at lifestyle conditions for which there are large, lucrative markets (eg, balding or erectile dysfunction) 5 , 6 . A Dutch study found that a DAA campaign increased disease‐related consultations and prescriptions for the advertiser's product for what may be considered an unimportant health issue 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DAA has been identified as a form of disease mongering or “widening the boundaries of treatable illness in order to expand markets for those who sell and deliver treatments” 4 . DAA is often directed at lifestyle conditions for which there are large, lucrative markets (eg, balding or erectile dysfunction) 5 , 6 . A Dutch study found that a DAA campaign increased disease‐related consultations and prescriptions for the advertiser's product for what may be considered an unimportant health issue 7 …”
mentioning
confidence: 99%
“…4 DAA is often directed at lifestyle conditions for which there are large, lucrative markets (eg, balding or erectile dysfunction). 5,6 A Dutch study found that a DAA campaign increased diseaserelated consultations and prescriptions for the advertiser' s product for what may be considered an unimportant health issue. 7 However, DAA can also provide information to help consumers identify symptoms and seek information about and treatment for previously untreated conditions.…”
mentioning
confidence: 99%
“…provision of health information) while its real purpose is to sell a product. 14,15 For example Mackenzie et al 15 describe DACs in Australia as "infomercials" which "evade the [DTC] advertising ban by masquerading as community education and not mentioning the drug itself " (p225).…”
Section: Disease Awareness Campaignsmentioning
confidence: 99%
“…There is concern that these advertisements will only be seen for diseases where there are larger and more lucrative markets, such as lifestyle conditions. 14,16 There are also claims that these advertisements generate unnecessary fear and encourage disease mongering and greater reliance on medications to solve social and behavioural problems. 6,17 However, DACs can also be seen as providing important information that assists consumers to identify symptoms and seek more information and/or treatment for previously untreated conditions.…”
Section: Disease Awareness Campaignsmentioning
confidence: 99%
“…In many countries where DTCA is not permitted, consumers are exposed to pharmaceutical company‐sponsored DAA, which is designed to create awareness of diseases and the availability of treatments. For DAA, a similar debate over its ethics and effects has occurred (Glatter, 2004; Mintzes, 2006). Moynihan and Henry (2006) argue that, like DTCA, DAA will encourage healthy people to believe they may require potentially unnecessary tests or medication.…”
Section: Introductionmentioning
confidence: 98%